2020
DOI: 10.2147/idr.s248342
|View full text |Cite
|
Sign up to set email alerts
|

<p>Co-Occurrence of <em>mcr-9</em> and <em>bla</em><sub>NDM-1</sub> in <em>Enterobacter cloacae</em> Isolated from a Patient with Bloodstream Infection</p>

Abstract: Background: Bloodstream infection (BSI) caused by carbapenem-resistant Enterobacteriaceae are potentially life-threatening related to poorer outcomes. Colistin is considered one of the lastresort treatments against human infections caused by multidrug-resistant (MDR) Gram-negative bacteria. Therefore, emergence of strains from the blood that co-harboring mcr and carbapenem resistance genes were considered as a serious problem. Purpose: In this study, two mcr-9-harboring MDR Enterobacter cloacae isolates BSI034… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
5
17
1
Order By: Relevance
“…Like the classical IncHI2 plasmids, the p1575-1 plasmid held a complete conjugative system, and the conjugation frequencies ranged from 0.5 × 10 −6 to 2 × 10 −6 per donor cell. The IncHI2-type conjugative plasmids harboring mcr-9 were also discovered previously, and the conjugation frequencies of those plasmid were 10 −4 (Lin et al, 2020) or 2.03 × 10 −7 (−5.42 × 10 −8 ) (Cha et al, 2020), which were similar to our findings. Through the analysis, we identified the complete conjugative modules on the plasmid p1575-1, strongly suggesting that p1575-1 could be transferred autonomously.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Like the classical IncHI2 plasmids, the p1575-1 plasmid held a complete conjugative system, and the conjugation frequencies ranged from 0.5 × 10 −6 to 2 × 10 −6 per donor cell. The IncHI2-type conjugative plasmids harboring mcr-9 were also discovered previously, and the conjugation frequencies of those plasmid were 10 −4 (Lin et al, 2020) or 2.03 × 10 −7 (−5.42 × 10 −8 ) (Cha et al, 2020), which were similar to our findings. Through the analysis, we identified the complete conjugative modules on the plasmid p1575-1, strongly suggesting that p1575-1 could be transferred autonomously.…”
Section: Discussionsupporting
confidence: 92%
“…Not like the blaNDM-1, which receives widespread attention, the bla SFO−1 gene is not included in the routine surveillance, but it could be an effective weapon that various gram-negative bacteria could use to resist β-lactams (Matsumoto and Inoue, 1999); therefore, the prevalence of the coexistence of the bla SFO−1 gene and carbapenemase genes might be underestimated. Some studies reported the coexistence of bla SFO−1 and bla NDM−1 β-lactamase genes and fosfomycin resistance gene fosA3 in Escherichia coli clinical isolate (Zhao et al, 2015) and the co-occurrence of mcr-9 and bla NDM−1 in Enterobacter cloacae (Yuan et al, 2019;Faccone et al, 2020;Lin et al, 2020). However, in this study, we not only found the coexistence of mcr-9 and bla NDM−1 , but also a rare gene bla SFO−1 was detected on the same transferable plasmid.…”
Section: Discussioncontrasting
confidence: 82%
“…In our three selected isolates, mcr-9 was demonstrated to be located on IncHI2/IncHI2A plasmids by the hybrid (Illumina-Oxford Nanopore) approach, together with other AMR genes conferring resistance to different antimicrobial classes, including the bla SHV −12 ESBL gene type detected in the two plasmids of pig origin, and different genes involved in heavy metals metabolism. Similarly, previous findings detected IncHI2-or IncHI2A-type plasmids in mcr-9 positive Enterobacteriaceae, often together with other resistance determinants (including HPCIAs) and to heavy metals mainly from human patients (Carroll et al, 2019;Chavda et al, 2019;Kieffer et al, 2019;Bitar et al, 2020;Faccone et al, 2020;Kananizadeh et al, 2020;Lin et al, 2020;Osei Sekyere et al, 2020;Soliman et al, 2020;Tsui et al, 2020;Umeda et al, 2020;Elbediwi et al, 2021;Marchetti et al, 2021;Sun et al, 2021), and also from animal (Börjesson et al, 2020;Yuan et al, 2019;Borowiak et al, 2020;Haenni et al, 2020;Leite et al, 2020), food (Borowiak et al, 2020;Sadek et al, 2020;Tyson et al, 2020), and environmental (Kamathewatta et al, 2020) sources. Few reports also described mcr-9 integrated into the chromosome of Citrobacter (Ribeiro et al, 2021) and Salmonella (Pan et al, 2020;Tyson et al, 2020) isolates, with a genetic context similar to the structure observed in mcr-9-harboring plasmid sequences, suggesting a possible mcr-9 transfer as a gene cassette between plasmids and chromosomes (Pan et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…The two plasmids IncX4 and IncI2 may increase the fitness of the host and become the major plasmid types driving the dissemination of the mcr-1 gene ( Wu et al, 2018 ). In the present study, we validated the presence of the mcr-9 gene commonly on large plasmids ( Lin et al, 2020 ). Colistin has been used for decades in veterinary medicine and as a last-resort drug to treat infections in humans ( Kempf et al, 2016 ).…”
Section: Discussionsupporting
confidence: 52%